Kvalitetskontroll av certifierade företag inom livsmedels-branschen - en jämförelse - Skager, Jonathan (2015)
The aim of the study was to provide an overview of how the quality control system of certified companies is structured in the food industry. But also to investigate, why the quality controls are necessary from both the authority and the certification bodies and investigate if the system can be streamlined. Quality controls of certi-fied companies in the food industry are carried out by both government agencies and certifying bodies. Quality control of the government agencies, also called offi-cial controls on food businesses, is something that is mandatory under European food law. However, it is not a legal requirement to comply with a food standard and to be certified against it by a certification body. But often in business-to-business relationships between companies, it is a requirement to follow a known standard and being certified against it by a certification body, to be seen as a po-tential partner. Quality is strongly linked to safe food and it is the government agencies goal to provide safe and honest food to consumers by there official con-trols. The control from the certification bodies depends on the standard orientation, which can be food safety but can also be environmentally oriented, ecological, etc. The study defines key concepts and organizations that form the basis of quality control in Sweden today. It also presents the actors who stand for quality control. Two interviews were conducted in the case study, one with Livsmedelsverket and one with the certification body KIWA Sweden AB. The results showed that both actors agreed that the system could be streamlined. But that efficiency will bring some obstacles that have to be overcome, in order to be implemented. The chapter also shows that the actors complement each other, in their quality controls. It is therefore concluded that cooperation between government agencies and the certifi-cation bodies could increase efficiency, but also improve controls further.